2003
DOI: 10.1186/cc1879
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 221COX-2 = cyclooxygenase-2; HSF = heat shock factor; HSP = heat shock protein; ICU = intensive care unit; IL = interleukin; NF = nuclear factor; OVLT = organum vasculosum of the laminae terminalis; TNF-α = tumor necrosis factor alpha.Available online http://ccforum.com/content/7/3/221 Fever occurs commonly in hospitalized patients. It is estimated that nosocomial fevers occur in approximately one-third of all medical patients at some time during their hospital stay [1]. In patients admitted to the intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…PBMC and endothelial cells ↓ NF-κB activation & cytokine production [191] Lung surfactant protein A Murine monocytes /macrophages ↓IL-10 production ↓TNF-α, IL-1α, IL-1β, NF-κB activation [192,193] Extracellular ATP Human monocytes ↓ MCP-1, TNF-α, increased IL-10 production [194] Filarial nematode protein ES-62 Murine macrophages ↓ TLR4 dependent IL-12 production [195] Bacterial superantigen Human monocytes ↑ TLR4 expression & LPS responsiveness [196] timepoints restores TNF-α production in low dose (0.5-10ng/ml) LPS tolerised human PBMC [180]. IL-12 can enhance IFN-γ production and partially restore TNF-α production in LPS tolerised PBMC.…”
Section: Factors That Modulate the Induction Of Tlr Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…PBMC and endothelial cells ↓ NF-κB activation & cytokine production [191] Lung surfactant protein A Murine monocytes /macrophages ↓IL-10 production ↓TNF-α, IL-1α, IL-1β, NF-κB activation [192,193] Extracellular ATP Human monocytes ↓ MCP-1, TNF-α, increased IL-10 production [194] Filarial nematode protein ES-62 Murine macrophages ↓ TLR4 dependent IL-12 production [195] Bacterial superantigen Human monocytes ↑ TLR4 expression & LPS responsiveness [196] timepoints restores TNF-α production in low dose (0.5-10ng/ml) LPS tolerised human PBMC [180]. IL-12 can enhance IFN-γ production and partially restore TNF-α production in LPS tolerised PBMC.…”
Section: Factors That Modulate the Induction Of Tlr Tolerancementioning
confidence: 99%
“…Another aspect of the inflammatory response is fever; proinflammatory cytokines such as IL-1 act via the hypothalamus to increase body temperature. Hyperthermia is associated with the release of heat shock proteins, which have been identified by a number of groups as potential ligands for TLR4 [42,230] ; hyperthermia is also associated with reduced NF-κB activity and diminished cytokine production, as seen in endotoxin tolerance [191]. Thus, it may be that the regulation of MyD88 dependent signalling serves a homeostatic role in limiting the febrile response.…”
Section: Tlr Tolerance: the Broader Thera-peutic Perspectivementioning
confidence: 99%
“…Fever, defined as an increase in body temperature above 38.3°C (100.4°F), is among the most frequently detected abnormal physical signs in critically ill patients related either to SIRS or infections [1,2]. Fever is associated with increased length of stay in general ICU patients and poorer outcomes in certain patient groups such as those with Traumatic Brain Injury (TBI), Subarachnoid Hemorrhage (SAH) or pancreatitis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of antipyretic drugs to diminish fever correlates with a 5% increase in mortality in human populations infected with influenza virus and negatively affects patient outcomes in the intensive care unit. 35 Preclinical studies in rabbits infected with rinderpest virus also found an increase in mortality when fever was inhibited with the antipyretic drug acetylsalicylic acid — 70% of acetylsalicylic acid-treated animals died as a result of infection as compared with only 16% of animals with a normal febrile response. 6 However, fever is not universally beneficial, particularly in cases of extreme inflammation where lowering, rather than raising body temperature has evolved as a protective mechanism.…”
mentioning
confidence: 99%